The evolving international economy - Chichilnisky, Graciela (Cambridge University Press, 1986)
This book focuses on the main issues of trade and development, and on the attainment of the major development goals generally espoused in the international community: rapid development in the Third World, sustained economic expansion in the industrial countries and the eradication of deep inequalities and of extreme poverty. It consists of four parts. The first three give an overall analysis of the world economy, with commentary and conclusions on major issues of trade and development. The fourth part provides the intuitive basis for the main results within the context of the formal models, and rigorous proofs are found in the references given to the technical literature. The analysis is descriptive, focusing on the particulars of market behaviour and tracing the ways in which markets respond to policies, in the belief that policies cannot be viewed in a vacuum, but must be confronted with the responses of the market. The interplay of domestic policies and international markets is a main feature of the authors' analysis
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Weltwirtschaft; International economic relations; Nord-Süd-Konflikt